Independence of the judge in the Republic of Kazakhstan - Akimbekova, S.A.; Kapatsina, V.I. (Bulletin of the Karaganda University “Law Series”, 2021)
The article considers the independence of judges as a criterion for evaluating the effectiveness of judges in the context of reforming the judicial system of the Republic of Kazakhstan. It is established that the principle of independence of judges from any interference in the process of making a court decision is enshrined in in-ternational and Kazakh normative legal acts. The principle of independence is multifaceted and involves the adoption of various ways to implement it. It is established that the formation of an adequate level of inde-pendence of judges is important for the administration of a fair trial and the creation of conditions for the res-toration of citizens ’ confidence in the judicial system. The purpose of the study is to determine the legal mechanism for ensuring the implementation of the constitutional principles of judicial independence. When working on the article, general scientific and private scientific methods of cognition, dialectical method, method of scientific analysis and generalization, formal legal method, system-structural method were used. The article attempts to reflect the fact that the practical maintenance of the independence of judges should be a priority of judicial reform, which will thereby increase the level of confidence in the judicial system in the minds of citizens. The analysis of the provisions of the scientific doctrine, the current regulatory acts of Ka-zakhstan, as well as the current stage of judicial reform implementation, undoubtedly shows that the inde-pendence of judges is indeed an important criterion for evaluating the effectiveness of courts in the context of judicial reform. That is why, in order to fulfill all the tasks of judicial reform, it is necessary to improve not only the objective side of the courts, but also to find new radical and operational ways to form independence as the basis for the administration of justice for all applicants for the position of judge and correct the idea of the independence of existing judges.